Utilization of hospital services for cancer care in Mexico - Juan Eugenio Hernández-Ávila; Lina Sofía Palacio-Mejía; Leonel González-González; Evangelina Morales-Carmona; Lucino Iván Espín-Arellano; Julián Alfredo Fernández-Niño; Alejandro Mohar-Betancourt; Mauricio Hernández-Ávila (Salud Pública de México, 2016)
Objective. To analyze the utilization of hospital services for cancer care by location, sex, age group and care institution in Mexico from 2004-2013. Materials and methods. Time series study from 2004-2013, based on administrative records of hospital discharges for cancer in the health sector, including the private sector. Results. The utilization rate increased significantly from 290 to 360 per 100 000 inhabitants. A total of 62% of hospital discharges related to malignant tumors were concentrated in eight types of cancer. Leukemia, breast and colorectal cancers almost doubled in the period. While lung cancer showed a decline among men, it increased among women. A total of 63.1% of cancer patients were women, and 81% of cases occurred in the public sector. From 2011, the Ministry of Health was the main provider of hospital services for cancer care. Conclusions. Increases in utilization were mainly found in the Ministry of Health, quite possibly as a result of the implementation of universal insurance.